Detarium microcarpum Guill. & Perr. fruit properties, processing and food uses. A review - TCHATCHA, Akouloukihi Damien; DJOSSOU, Andriano Jospin; Tchobo, Fidèle Paul; SOUMANOU, MANSOUROU MOHAMED; Houndonougbo, Frederic; PAUCEAN, Adriana (My University, 2022)
Detarium microcarpum is a woody fruit plant, widely found in the dense dry and clear forests of sub-Saharan Africa. This review presents the nutritional and functional properties of D. microcarpum fruits pulp and seed, as well as their uses in food products. Literature. The two edible parts of the fruit of D. microcarpum are pulp and seed. These pulp and seed have an almost identical carbohydrate content (40.2-66.1%). Pulp contains proteins (2.9-6.1%), lipids (0.7-2.2%), and minerals: magnesium (51-84 mg.100g-1), potassium (1,017 mg.100g-1) and vitamins (vitamin C: 4.6-4.7 mg.100g-1). Seed also contains proteins (34.5-37.1%), lipids (23%), minerals and vitamins (vitamin C: 9.3-28.1 mg.100g-1). Seed powder exhibits functional properties such as bulk density (0.5-0.9 g.cm-3), water absorption capacity (3.5-11.7 ml.g-1), oil absorption capacity (0.7-3.1 ml.g-1), solubility (2-3%), emulsion capacity (4.3-4.4%), emulsion stability (3.4-3.5%), foaming capacity (8.7-8.8 cm3 ) and foam stability (7.0-9.3 cm3 ); it also improves the viscosity of dough. Pulp is used in juice and jam, while seeds are used as a stabilizer or as a thickener in juice, jam, tomato sauce, traditional soup, white bread, raw beef burger, and ice cream. Conclusions. Most studied works on the seed of D. microcarpum did not explore beyond the properties of its gum. Likewise, those on the pulp only approached its use in juice and jam. Therefore, it presents a large possibility for research in the context of the formulation of foods containing D. microcarpum fruits.
Keywords: Food composition; food processing; fruit trees; functional foods; fruit products